2014
DOI: 10.1063/1.4894865
|View full text |Cite
|
Sign up to set email alerts
|

Scaling behavior of hysteresis in multilayer MoS2 field effect transistors

Abstract: Extrinsic hysteresis effects are often observed in MoS2 field effect devices due to adsorption of gas molecules on the surface of MoS2 channel. Scaling is a common method used in ferroics to quantitatively study the hysteresis. Here, the scaling behavior of hysteresis in multilayer MoS2 field effect transistors with a back-gated configuration was investigated. The power-law scaling relations were obtained for hysteresis area (⟨A⟩) and memory window (ΔV) with varying the region of back-gate voltage (Vbg,max). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 26 publications
6
79
0
Order By: Relevance
“…However, the photo-excited holes in MoTe 2 get trapped mostly at the MoTe 2 -SiO 2 interface as well as at the defect states inside the MoTe 2 closer to its valence band, which are mostly immobile (reflected in poor mobility <1 cm and hence do not participate in conduction. [32][33][34][35] This also explains why it takes almost a day to come back to its initial value after the light is off (Fig. 3c).…”
Section: Discussionmentioning
confidence: 82%
“…However, the photo-excited holes in MoTe 2 get trapped mostly at the MoTe 2 -SiO 2 interface as well as at the defect states inside the MoTe 2 closer to its valence band, which are mostly immobile (reflected in poor mobility <1 cm and hence do not participate in conduction. [32][33][34][35] This also explains why it takes almost a day to come back to its initial value after the light is off (Fig. 3c).…”
Section: Discussionmentioning
confidence: 82%
“…For large negative gate bias these trapped electrons are released from adsorbed molecules into the MoS 2 channel which reduces V TH . 19 This leads to a positive ΔV TH and therefore, clockwise hysteresis. However, our results do not support adsorbate mediated hysteresis because, (1) for measurements done in a dry vacuum/ nitrogen ambiance increasing the temperature should reduce the amount of absorbates on MoS 2 , and hence decrease the hysteresis until it collapses (shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 and Table 1) considered in previous studies. [16][17][18][19]22,23,25 Adsorbate mediated hysteresis mechanism 18,19 is shown in Fig. 3a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous report, we showed that the hysteresis was exponentially proportional to the range of V bg . 22 The field-effect mobility (µ FE ) of MoS 2 FETs increased significantly when high-κ Al 2 O 3 replaced SiO 2 as the back-gate dielectrics (Fig. 2(d)).…”
mentioning
confidence: 99%